Prevalence of respiratory bacterial pathogens and associated management factors in dairy calves in Taiwan - LEE, Hsu-Hsun; THONGRUEANG, Natcha; LIU, Shyh-Shyan; HSU, Huan-Yu; TSAI, Yi-Lun (Journal of Veterinary Medical Science, 2022)
This study aimed to investigate the prevalence at both farm-level and calf-level and to identify the risk factors of respiratory bacterial pathogens in dairy calves in Taiwan. The status of bovine respiratory disease (BRD) was evaluated by using the Wisconsin scoring system from a total of 400 pre-weaned calves from 32 different farms in Taiwan, then the nasopharyngeal swabs were collected. The prevalence of respiratory pathogens was 84.37% at farm-level and 45.50% at calf-level, and Pasteurella multocida (P. multocida) was the most prevalent pathogen. The presence of Mycoplasma bovis (M. bovis), P. multocida, Mannheimia haemolytica (M. haemolytica) and Histophilus somni (H. somni) were all higher in BRD positive calves than BRD negative calves, but only in H. somni was significant (P<0.001). Then nine farm management risk factors were analyzed by using multivariate logistic regression models to determine the risk factors of respiratory bacterial pathogens (farm and calf-level). In the result at farm-level, only unheated colostrum was significantly associated with pathogen positive farms (Odds Ratio (OR)=11.43). At calf-level, the predominant risk factor for each pathogen, M. bovis, P. multocida, M. haemolytica and H. somni, was late first colostrum feeding (OR=272.82), unheated colostrum (OR=3.41), waste milk feeding (OR=6.59) and high pneumonia treatment cost (OR=2.52), respectively. For effective preventive measures, farmer education on milk and colostrum feeding are urgently warranted.